Superoxide Dismutase 1 Loss Disturbs Intracellular Redox Signaling, Resulting in Global Age-Related Pathological Changes - Watanabe, Kenji (Hindawi Publishing Corporation, 2014)
Aging is characterized by increased oxidative stress, chronic inflammation, and organ dysfunction, which occur in a progressive and irreversible manner. Superoxide dismutase (SOD) serves as a major antioxidant and neutralizes superoxide radicals throughout the body. In vivo studies have demonstrated that copper/zinc superoxide dismutase-deficient (Sod1(−/−)) mice show various aging-like pathologies, accompanied by augmentation of oxidative damage in organs. We found that antioxidant treatment significantly attenuated the age-related tissue changes and oxidative damage-associated p53 upregulation in Sod1(−/−) mice. This review will focus on various age-related pathologies caused by the loss of Sod1 and will discuss the molecular mechanisms underlying the pathogenesis in Sod1(−/−) mice.